Associations Between Daily Physical Activity and Motor Skill Competence Among Preschool Children - Ahmad, Nadhira Yasmine; Noviansyah, Aulia; Ginting, Rapael; Manalu, Marselinus V.Y; Gomagel, Yoel; Surbakti, Surbakti; Ritrit Yanto Zai, Ritrit Yanto Zai (Journal of Foundational Learning and Child Development, 2025)
Purpose of the study: This study examined the associations between objectively measured daily physical activity (PA) and motor skill competence (MSC) among Indonesian preschool children, addressing the critical gap in understanding early childhood movement behaviors in Southeast Asian contexts. Materials and methods: Eighty-three preschool children (40 boys, 43 girls; mean age 5.2 ± 0.7 years) from TKQ Baiturrahman Medan, Indonesia, participated in this cross-sectional study. Daily PA was measured using ActiGraph GT3X accelerometers worn for seven consecutive days. MSC was assessed using the Test of Gross Motor Development-3 (TGMD-3), evaluating locomotor and ball skills. Pearson correlations and multiple linear regression analyses examined associations between PA variables and MSC scores, controlling for age and gender. Results: Children accumulated 58.4 ± 18.2 minutes of moderate-to-vigorous physical activity (MVPA) daily and 8,847 ± 2,156 steps/day. Mean total MSC standard score was 92.3 ± 14.6 (locomotor: 9.2 ± 2.8; ball skills: 8.9 ± 3.1). Significant positive correlations emerged between daily MVPA and total MSC (r = 0.41, p < 0.001), locomotor skills (r = 0.38, p < 0.001), and ball skills (r = 0.36, p = 0.001). Step count correlated moderately with MSC (r = 0.34, p = 0.002). Multiple regression revealed that MVPA significantly predicted MSC (β = 0.39, p < 0.001), explaining 23% of variance after controlling for covariates. Children in the highest MVPA tertile demonstrated significantly higher MSC scores than those in the lowest tertile (98.7 ± 12.4 vs. 84.6 ± 14.2, p < 0.001). Conclusions: Daily PA, particularly MVPA, demonstrates significant positive associations with motor skill competence in preschool children. These findings underscore the importance of promoting adequate PA opportunities in early childhood education settings to support fundamental motor development. Early childhood educators and policymakers should prioritize structured and unstructured PA experiences to facilitate optimal motor competence development during this critical developmental period.